2001
DOI: 10.1039/b104874k
|View full text |Cite
|
Sign up to set email alerts
|

An assay for the enzyme N-acetyl-β-d-glucosaminidase (NAGase) based on electrochemical detection using screen-printed carbon electrodes (SPCEs)

Abstract: An electrochemical assay for the enzyme N-acetyl-beta-D-glucosaminidase (NAGase) is described, using bare screen-printed carbon electrodes (SPCEs). The enzyme substrate, 1-naphthyl-N-acetyl-beta-D-glucosaminide, was added to the NAGase-containing sample under hydrodynamic conditions and was hydrolysed to 1-naphthol, which was monitored amperometrically at an Eapp of +650 mV versus SCE. A pH study revealed the apparent Vmax for the assay to occur at pH 4.5. corresponding to an apparent substrate Km of 0.28 mM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…Enzymes Pemberton et al (2001) reported laboratory experiments with SPCE, having a square working area of 9 mm were printed from D14 ink formulation (Gwent Electronic Materials Ltd, Gwent, Wales) onto a PVC base. Automatic On-Line Analysis Of Milk Constituents Using Biosensors Electrochemical measurements were made under hydrodynamic conditions using a three-electrode system contained within a modi¢ed cylindrical oxygen cell and using an analyte volume of 2 ml.…”
Section: Ionic Concentrationmentioning
confidence: 99%
“…Enzymes Pemberton et al (2001) reported laboratory experiments with SPCE, having a square working area of 9 mm were printed from D14 ink formulation (Gwent Electronic Materials Ltd, Gwent, Wales) onto a PVC base. Automatic On-Line Analysis Of Milk Constituents Using Biosensors Electrochemical measurements were made under hydrodynamic conditions using a three-electrode system contained within a modi¢ed cylindrical oxygen cell and using an analyte volume of 2 ml.…”
Section: Ionic Concentrationmentioning
confidence: 99%
“…Those that do exist mostly automate or augment manual serological tests for a single disease; examples include "electronic noses" for detecting bovine tuberculosis [11] or ketosis [12]; a chemical sensor to detect mastitis from milk samples [13]; and detection of ovulation in dairy cows using chemical sensors in milk samples [14] or via transrectal ultrasonography [15]. There are no sensor systems that respond to a wide variety of diseases in the literature on cattle production; this, however, is precisely what the feedlot operator needs.…”
Section: A Livestock Disease Managementmentioning
confidence: 99%
“…For instance, oxido/reduction process of 1-naphthol, which is a substrate of NAGase can be easily detected and quantified using carbon electrodes. Pamberton et al [ 67 ] have reported an electrochemical sensor based on a screen-printed carbon electrode which detected NAGase protein in milk samples with a limit of detection of 10 mU/mL. Surface plasmon resonance was employed to monitor binding of haemoglobin to haptoglobin immobilized on the surface of the chip [ 68 ].…”
Section: Detection Of Mycoplasma and Other Bovine mentioning
confidence: 99%